The Lewis‐Base‐Stabilized Diphenyl‐Substituted Arsanylborane: A Versatile Building Block for Arsanylborane Oligomers. Issue 62 (17th October 2018) - Hegen, Oliver; Virovets, Alexander V.; Timoshkin, Alexey Y.; Scheer, Manfred
Abstract: The synthesis and properties of the diphenyl‐substituted arsanylborane Ph2 AsBH2 SMe2 (1 ) and Ph2 AsBH2 NMe3 (2 ) stabilized by a Lewis base (LB) were reported. These compounds were obtained by reaction of KAsPh2 with IBH2 −LB (LB=SMe2, NMe3 ). Compounds1 and2 were used as starting materials for oligomeric/ polymeric arsinoboranes. The neutral species, H3 B−Ph2 AsBH2 NMe3 (3 ) and Br3 B−Ph2 AsBH2 NMe3 (4 ), were synthesized by reaction with H3 B and Br3 B, respectively. Upon reaction with IBH2 −LB (LB=SMe2, NMe3 ), the cationic oligomeric group‐13/15‐based compounds [(Me3 NBH2 AsPh2 BH2 NMe3 )]I (5 ) and [H2 B(Ph2 AsBH2 NMe3 )2 ]I (6 ) were obtained. All compounds were completely characterized. In addition, the oxidation of Ph2 AsBH2 NMe3 with chalcogens was studied. The sulfur Ph2 As(S)BH2 NMe3 (7 b ) and selenium Ph2 As(Se)BH2 NMe3 (7 c ) oxidation products were both isolated and fully characterized, whereas the bis(trimethylsilyl)peroxide oxidated arsinoborane Ph2 As(O)BH2 NMe3 (7 a ) was not stable enough and could only be characterized in solution. DFT computations supported the decomposition pathway of this compound. Abstract : Bigger brothers : The synthesis and reactivity of the new arsanylboranes Ph2 AsBH2 NMe3 and Ph2 AsBH2 SMe2 are presented. Although the coordination behavior towards Lewis acids is similar to that of the phosphorus analogue, oxidation with chalcogens and oligomerization reactions differ significantly.